Isolation and Characterization of Chemical Compounds from Achyranthes Bidentata for Evaluation of Anti-Parkinson’s Activity Through In-Silico Approach: Pharmaceutical Science-Pharmaceutics - Thapa, Rahul; Shikha; Arya, Girish Chandra; Arora, Saahil (International Journal of Life Science and Pharma Research, 2023)
Achyranthes bidentata has been used to treat asthenia of lower limbs, painful backs & knees, atherosclerosis & many other ailments for a very long time. It is found that A. bidentata has many pharmacological activities such as anticancer & immunomodulatory activities, antiosteoporosis, neurotrophic & neuroprotective effects. In Chinese medicine system it is used for abortion. The main chemical components of A.bidentata are sterones & saponins which are recognized as main active compounds. The aim of this investigation is to isolate and characterize the chemical compounds from the aerial part of A.bidentata for assessing the Anti-Parkinson’s activity through in-silico studies of isolated phytoconstituents. In this present work, aerial parts of A.bidentata were used for the potential of anti-parkinson’s activity. The phytochemical investigation revealed that it is rich in alkaloids, terpenoids and saponins. The crude ethanol extract of A.bidentata was partitioned with n-hexane, ethyl acetate, n-butanol, and water. Ethyl acetate fraction much revealed the presence of phytoconstituents carried out with isolation. Compounds identified by NMR, MS and UPLC analysis were oleanolic acid and 5-hydroxymethyl furfural. Molecular docking studies of designed compounds have been performed to investigate interaction with Dj-1/RS associated with PD. This research will be helpful in completing information on the identification and authentication of A. bidentata, and the use of aerial parts of A.bidentata for testing their anti-Parkinson's activity, which will aid in the development of an alternative treatment to allopathic drugs, which have serious side effects. The extraction methods for A.bidentata can be improved with the help of this study. Keywords: , , ,